Review: A Perspective Use and Misuse of Antibiotics - Prasad, P. Dharani (Asian Journal of Pharmaceutics (AJP), 2023)
Antibiotics are the most active chemotherapeutics among drugs; they exert their therapeutic effect by antagonizing the growth of bacteria. Since 1910 many antibiotics have been developed with different mechanisms of action including: (1) Inhibition of bacteria’s cell wallsynthesis; this class of antibiotics includes vancomycin and β-lactam antibiotics such aspenicillins, cephalosporins, and carbapenems, (2) inhibition of protein synthesis including tetracyclines, aminoglycosides, macrolides, and chloramphenicol, and (3) DNA synthesis inhibitors such as fluoroquinolones and sulfonamides that inhibit folic acid synthesis. In this chapter, we describe the three antibiotic classes, their mechanism of action, clinical uses, side effects, and their resistance by different bacteria